Implications of High-Sensitivity Cardiac Troponin I in Cardiology Clinical Practice - Khaw, C.S.; Loretta, L.L.C.; Amirul Fadhli, H.; Azzlee, M.; Yeo, John; Lim, H.S.; Said, A. (Elsevier, 2017)
Background: High sensitivity troponin (hsTn) has better sensitivity for myocardial tissue injury detection compared to standard troponin assays, despite lower diagnostic specificity and lack of hsTn assay standardization. Objectives: To examine implications of introducing hsTnI in clinical practice. Methods: We retrospectively collected information of patients presented to a single tertiary cardiac referral centre with suspected acute coronary syndrome (ACS), who had ≥1 hsTnI sample (Abbott ARCHITECT STAT), from 1st June 2016-17th August 2016. Upper range limit (URL), i.e. 99th percentile, was defined as 34.2 ng/L, 15.6 ng/L and 26.2 ng/L for male, female and both gender (“overall”) respectively. Patients were divided into 4 groups - Group 1: hsTnURL but b3 times URL, Group 3: hsTn between 3-5 times URL and Group 4: hsTnN5 times URL. Results: Data from 366 patients was analysed: 227(62.0%), 34(9.3%), 13(3.6%), 92(25.1%) in Group 1, 2, 3 and 4 respectively. In Group 1 to 4, the proportion of ACS was 8.8%, 38.0%, 53.8%, 82.6% and proportion of MI were 0.8%, 29.4%, 53.8%. 82.6%. By using N5 times URL as cut-off, hsTnI has higher specificity and PPV, but lower sensitivity and NPV in diagnosis of ACS {(sensitivity:0.66, specificity:0.0.94, PPV0.83, NPV0.85), with ROC curve AUC:0.896, pb0.001, 95% CI:0.861-0.931}. Our analysis showed serial paired hsTn samples increase the PPV of hsTn to detect ACS. There was no significant difference between using hsTn URL “overall” or “gender-specific” for ACS diagnosis. Kaplan-Meier analysis showed 30-day all-cause mortality in the group with maximal hsTn value NURL is significant higher (pb0.001). Multiple-logistic regression showed that URL of hsTn was an independent variable for 30-day all-cause mortality (p<0.001). Conclusions: Introducing hsTnI has led to the recognition of a large proportion of patients with minor cardiac troponin increases (above URL of 99th percentile but b5 times URL), the majority of whom do not have ACS or MI. There is no significant difference in using “overall” and “gender-specific” URL in diagnosing ACS. Using 5 times above URL and serial hsTn will increase PPV to detect ACS. Maximal HsTn value N99th percentile is independently associated with 30-day all-cause mortality.